PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PRAKTIK MANAJEMEN LABA RIIL ( Studi Empiris pada Perusahaan Sub Sektor Perdagangan Besar yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Dimas Muhammad Ismail; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of Good Corporate Governance on real earnings management practices carried out by companies. The independent variables used in this study are the size of the board of commissioners, the proportion of independent commissioners, managerial ownership, institutional ownership, audit committee size, and audit committee meetings as a proxy for Good Corporate Governance. The dependent variable used in this study is real earnings managements.          The sample used in this study was selected using purposive sampling and obtained a final sample of 49 large trading sub-sector companies listed on the IDX for the 2017-2019 period. Hypothesis testing in this study was conducted using multiple linear regression analysis.          The test results show that the proportion of independent commissioners, managerial ownership, the size of the audit committee and audit committee meetings have no significant effect on the real earnings management carried out by the company. The size of the board of commissioners has a significant negative effect on the company's real earnings management, while institutional ownership has a significant positive effect on the company's real earnings management.